2003
DOI: 10.1128/aac.47.4.1343-1346.2003
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal aadD2 Encodes an Aminoglycoside Nucleotidyltransferase in Bacillus clausii

Abstract: Bacillus clausii SIN is one of the four strains of B. clausii composing a probiotic administered to humans for the prevention of gastrointestinal side effects due to oral antibiotic therapy. The strain is resistant to kanamycin, tobramycin, and amikacin. A gene conferring aminoglycoside resistance was cloned into Escherichia coli and sequenced. The gene, called aadD2, encoding a putative 246-amino acid protein, shared 47% identity with ant(4)-Ia from Staphylococcus aureus, which encodes an aminoglycoside 4-O-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 23 publications
(15 reference statements)
2
32
0
2
Order By: Relevance
“…We have recently shown that resistance to aminoglycosides was due to the synthesis of an aminoglycosideinactivating enzyme encoded by an aadD2 chromosomal gene (3). In this study, we have shown that resistance to macrolides was associated with the presence of an erm (34) gene that has not been characterized or found in other bacteria so far.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…We have recently shown that resistance to aminoglycosides was due to the synthesis of an aminoglycosideinactivating enzyme encoded by an aadD2 chromosomal gene (3). In this study, we have shown that resistance to macrolides was associated with the presence of an erm (34) gene that has not been characterized or found in other bacteria so far.…”
Section: Discussionmentioning
confidence: 69%
“…The B. clausii probiotic strains are resistant to clinically important antibiotics, including macrolides and aminoglycosides (3,22). We have recently shown that resistance to aminoglycosides was due to the synthesis of an aminoglycosideinactivating enzyme encoded by an aadD2 chromosomal gene (3).…”
Section: Discussionmentioning
confidence: 99%
“…B. clausii possesses an intrinsic resistance to the penicillins, cephaolosporins, aminoglycosides, and the macrolides; an acquired resistance to tetracycline and chloramphenicol and finally a resistance to rifampicin due to a chromosomal mutation. Of note, none of the genes involved in these mechanisms are associated to a known mobile plasmidic element, placing the possibility of horizontal transfer at the lowest degree (43,44).…”
Section: The Biochemical Properties Of B Clausiimentioning
confidence: 99%
“…The chromosomal location of the ␤-lactamase genes was determined in whole-cell DNAs of B. clausii NR and ATCC 21537 by using the I-CeuI technique (4,24). Electrophoresis was performed with a CHEF-DRII apparatus (Bio-Rad) used for pulsed-field gel electrophoresis (PFGE), as described elsewhere (24), at 14°C and 5 V/cm with a 120°switch angle, with one linear switch ramp of 20 to 120 s for 15 h and a second one of 60 to 100 s for 12 h. The sizes of the I-CeuI-generated fragments were determined by comparison with those of E. coli K-12 (24).…”
Section: Methodsmentioning
confidence: 99%
“…Resistance to erythromycin is one of the reported features of B. clausii (3,10), due to the presence of an erm-related gene (5). B. clausii strains are also resistant to penicillin G, cephalothin, and cefotaxime (4).…”
mentioning
confidence: 99%